Sex-disaggregated agricultural extension and weather variability in Africa south of the Sahara - Azzarri, Carlo; Nico, Gianluigi (Elsevier, 2022)
Climate change and extreme weather shocks pose serious threats to a number of agricultural outcomes, including agricultural production, productivity, and income, especially when households depend heavily on this activity. Agricultural extension and rural advisory services are key instruments in promoting technical change, advancing agricultural productivity growth and, ultimately, improving farm livelihoods, and are expected to mitigate the negative effects of climate change and extreme weather shocks. Their mitigation effects, however, may vary depending on the sex of the recipient. This paper investigates the role of sex-disaggregated agricultural extension recipients in contexts where agricultural performance of farm households is affected by weather variability. To this aim, we match multiple rounds of panel microdata from the nationally representative, consumption-based Living Standards Measurement Study -Integrated Surveys on Agriculture (LSMS-ISA), collected in four sub-Saharan African countries, with remote sensing data on biophysical dimensions over a long-term horizon as well as year-specific weather shocks. To our knowledge, this is the first time that a micro-level dataset with individual-level information on agricultural extension services’ recipients has been assembled and examined to investigate the effects of extreme weather shocks and climate change. Applying panel data econometric estimators, the study finds that agricultural extension and advisory services translate into higher agricultural performance of farm households where women are also among the beneficiaries, as compared to non-beneficiaries and households where beneficiaries are men only. Moreover, these services can mitigate the negative effects of weather variability and climate change, controlling for country and time fixed effects as well as holding all other variables constant. These results call for national and international policies and interventions strengthening rural advisory services, especially targeted to women in settings where household livelihoods are predominantly agriculture-based and weather variability and shocks are expected to negatively affect farming activities.